Identification of Job Preferences of Youth and the Related Factors in Isfahan City - Malihe Alimondegari; Hajiieh Bibi Razeghi Nasrabad; Alireza Bakhtiari (پژوهش‌های راهبردی مسائل اجتماعی ایران, 2021)
The optimal use of human resources in the labor market requires recognizing the variables that affect individuals' job preferences. Job preferences indicate the hierarchical superiority of some characteristics of a job over other characteristics related to an individual (Amabaill, 1994: 953). In fact, job preferences demonstrate what job each person expects to get in the future according to his/her skills and education. Preferring a decent job in accordance with an individual’s skills, interests, and expertise can flourish his/her talents, accelerate the process of performing tasks, increase productivity in the society and accelerate its development wheel. However, if the job choice is not done properly, it could lead to job dissatisfaction, reduced efficiency, enhanced costs in the workplace, weakening of values, norms, and organizational goals in relation to individuals, and social distrust (Moeidfar et al., 2005: 130). The range of job characteristics includes its external and internal aspects. The external aspect is related to income, security, and job position. The internal aspect is related to the mental understanding of whether the job is inherently interesting and if it is good for the community or for others. Also, in another classification of jobs, the main features related to the aspects of job autonomy, such as independent employment opportunities and control of work organization or working time, are considered (Davoine, Erhel, and Guergoat, 2008; Handel, 2005; Ros, Schwartz, and Surkiss, 1999). Although it has been assumed that economic motivation is often important to the employed person, much research in the social sciences has shown significant changes in job-related values. The present research focused on job capacity for providing social integration, social structure of daily life, and a creative and innovative atmosphere, giving meaning to life, and contributing to the development of the society (Jahoda, 1982). Job preferences were first measured by Jurgensen at the Minnesota Gas Company in 1945 (Jurgensen, 1945) and its questionnaire was completed in 1975 (Agent, 1975). The agent-based job preference questionnaire states what one’s job preferences are in order of priority. The questions are related to promotion opportunities, type of company (public, private, or cooperative), income, type of job, job security, salary and benefits, working hours, supervisor, co-workers, and working conditions. Amabil et al. (1994) divided job preferences into two categories: internal and external preferences. Internal preferences lead to a particular job due to internal feelings like desire to succeed or desire to gain experience. Based on external preferences, a person tends to a particular profession to access external factors, such as encouragement and avoidance of punishment. In recent years, various studies have focused on job preferences in terms of importance of work quality and higher levels of job satisfaction (Pichler and Wallace, 2009; Westover, 2012), life satisfaction (Drobnič, Beham, and Präg, 2010), physical health (Aronsson and Blom, 2010), and welfare (Esser, 2017; Eurofound, 2012). Overall, individuals’ job preferences seem to be of fundamental importance in terms of work motivation and individual well-being (Esser and Lindh, 2018: 143).The main purpose of this study was to investigate young people’s job preferences and identify the socio-demographic characteristics affecting their job preferences. Also, the system of young people’s job preferences was studied and the socio-demographic characteristics affecting it were identified in Isfahan as one of the central and major cities of Iran. According to the Statistics Center of Iran (2016), the population of Isfahan Province was equal to 5120850 people, of which 1629475 people (31.5%) were in the age group of 18-35 years. Also, the economic growth was 46.1% based on the results of the Labor Force Survey (2020).  Materials & MethodsThis research was based on a survey method. The data collection tool was a researcher-made questionnaire and the sample size was 400 young people aged 18-35 years in 2020. Also, a multi-stage cluster sampling proportional to the population size was undertaken using quotas.Despite the limitations of Covid-19 pandemic in 2020, the questionnaires were completed in full compliance with all health protocols during the absence of critical outbreak (orange and red). For data analysis, SPSS software (version 22) and AMOS software were applied. In addition, statistical tests, including mean comparison (t-test and one-way analysis of variance), calculation of correlation coefficient (Pearson and Spearman), and regression and structural equation model were employed. The dependent variable of the research was job preference and the independent variables included education, parents' education, gender, socio-economic class, future job security, method of choosing a job, work experience, and family and friends’ guidance.In this study, to assess the young people’s job preferences, an agent questionnaire with the two items of degree of difficulty and comfort of job (having a job without stress) was utilized. In addition, 4 general factors were summarized by using factor analysis. The first factor, the economic dimension of work, which was confirmed by Cronbach's alpha coefficient of 0.762, included the items of income, job security, job benefits, and opportunity of job promotion. Considering the work-family balance, the second factor, which was confirmed by Cronbach's alpha coefficient of 0.689, included working hours during the week, possibility of balancing between work and family affairs, and workplace conditions such as distance or proximity to the residential place, leave benefits, and type of company (public, private, or cooperative). The third factor, which dealt with the social dimension of work and its characteristics and was confirmed by Cronbach's alpha coefficient of 0.689, consisted of co-workers’ moral characteristics, having a good and considerate supervisor, and having a job without stress and risks. The fourth factor, which was confirmed by Cronbach's alpha coefficient of 0.641, was the inherent nature of job, including the degree of difficulty and comfort of job, type of job, job interest, and possibility of increasing a sense of self-fulfillment. Discussion of Results & ConclusionsThe findings showed that the female respondents considered the dimensions of the nature of work and balance between work and family, the economic dimension of work, and the social dimension of work as important factors, while the male respondents regarded the economic dimension of work, the dimensions of the nature of work and work balance between work and family, and the social dimension of work, respectively. In fact, the priorities of the female respondents in choosing a job were interest, income, job security (having a job without stress and job risks), job conditions (work place and time), type of company (public, private, or cooperative), and the opportunity for promotion or career advancement, respectively. The priorities of the male respondents were the income, sense of job security, interest, job benefits, working conditions and hours, degree of difficulty and comfort, moral characteristics of colleagues, and type of company, respectively.The findings indicated the significant relationships of the variables of education, family and friends’ guidance, work experience, socio-economic class, job security, job selection, and gender with the mentioned dimensions of job preferences. Based on the multivariate analysis performed by using the regression and structural equation model, the variables of job security, job selection, education, and gender were identified as determinants of the dimensions of job preferences. According to the research results, it is recommended that academic career counseling be provided in accordance with the needs of the labor market, as well as  job security by the employer since employers can be satisfied with their employments when guiding applicants to choose their desired jobs.